Methodological issues in assessing change in dietary intake and appetite following gastric bypass surgery: A systematic review. (1st February 2021) - Redpath, Tamsyn L.; Livingstone, M. Barbara E.; Dunne, Aoibheann A.; Boyd, Adele; le Roux, Carel W.; Spector, Alan C.; Price, Ruth K.
Summary: Gastric bypass surgery is an effective long‐term treatment for individuals with severe obesity. Changes in appetite, dietary intake, and food preferences have all been postulated to contribute to postoperative body weight regulation, however, findings are inconsistent. The aim of this systematic review was to evaluate the current literature on changes in dietary intake and appetite following gastric bypass surgery, in the context of the methodology used and the analysis, interpretation, and presentation of results. Four databases were systematically searched with terms related to "gastric bypass surgery, " "appetite, " and "dietary intake, " and 49 papers ( n = 2384 patients after gastric bypass) were eligible for inclusion. The evidence indicated that only a reduction in overall energy intake and an increase in postprandial satiety are maintained beyond 6‐month post‐surgery, whereas relative macronutrient intake and premeal hunger remain unchanged. However, available data were limited by inconsistencies in the methods, analysis, presentation, and interpretation of results. In particular, there was a reliance on data collected by subjective methods with minimal acknowledgment of the limitations, such as misreporting of food intake. There is a need for further work employing objective measurement of appetite and dietary intake following gastric bypass surgery to determine how these mechanisms may contribute to weight regulation in the longer term.